Water vapour changes and atmospheric cluster ions - Harrison, R; Aplin, K (2007)
Properties of small ions in atmospheric air have been investigated using a modern ion spectrometer with co-located meteorological and atmospheric electrical measurements, in urban air at Reading during May and June, (days 147-154) 2005. The ion spectrometer's programmed measurement sequence determined the mean ion currents and their variability, permitting derivation of positive and negative ion number concentrations, and their associated mean mobilities, on a ∼ 30 min cycle. The ion measurements were validated by comparing the derived air conductivity with the nearby atmospheric electrical potential gradient, and both these independently measured parameters correlated closely under fair weather conditions. Histograms of the mean mobility for positive (μ+) and negative (μ-) ions across the 7 days of measurement showed μ- > μ+, i.e. that the negative ion mass was less than that of positive ions. Adjacent air humidity measurements were used to analyse the mobility data. Using the median water vapour pressure of 4.1 hPa as a threshold, the mean μ+ was found to be significantly lower when vapour pressures were above the threshold, but there was no significant change in μ- with vapour pressure. As the effect on positive ions remains present in strong sunlight, weak sunlight, and darkness, it is unlikely to be solely of photochemical origin but, more probably, related to changes in ion hydration. There is therefore an asymmetric response of positive and negative ions to water vapour. This will influence the aerosol electrification in fogs and clouds, and modify the radiative response of hydrated ion clusters. © 2007 Elsevier B.V. All rights reserved.